2006
DOI: 10.2478/s11772-006-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

Third-generation sensors for night vision

Abstract: Third generation sensors are under development to enhance capabilities for target detection and identification, threat warning, and 3D imaging. Distinct programs for both cooled HgCdTe and uncooled microbolometer devices are part of this thrust. This paper will describe the technology for HgCdle two-colour, high-definition imaging sensors and threat warning devices, avalanche photodiode arrays for 3D imaging, and the supporting technology being developed to enhance the readouts that support these devices. Unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 20 publications
(26 reference statements)
0
24
0
1
Order By: Relevance
“…4 Since its first synthesis, HgCdTe has given rise to three different generations of devices. [5][6][7] The first relied on linear arrays with up to 180 elements of photoconductive (PC) detectors for scanning systems generated images. The second generation consists of two-dimensional arrays of photovoltaic (PV) pixels which are scanned electronically to build the image.…”
Section: Introductionmentioning
confidence: 99%
“…4 Since its first synthesis, HgCdTe has given rise to three different generations of devices. [5][6][7] The first relied on linear arrays with up to 180 elements of photoconductive (PC) detectors for scanning systems generated images. The second generation consists of two-dimensional arrays of photovoltaic (PV) pixels which are scanned electronically to build the image.…”
Section: Introductionmentioning
confidence: 99%
“…Future space missions such as Euclid (Amiaux et al 2012) and WFIRST (Spergel et al 2013) plan on utilizing this detector technology, which provides access to high redshift objects and structures in our universe. The performance of HgCdTe NIR detectors (Norton 2002) has been significantly improved during the last two decades and the widespread adoption of this technology by the astronomical community has led to major characterization and testing efforts. Laboratory studies and use on telescopes have revealed detailed performance features and have contributed to a better understanding of these devices (e.g., Finger et al 2004;McCullough et al 2008;Moore 2006;Barron et al 2007;Biesiadzinski et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Multispectral capabilities are highly desirable for advanced infrared (IR) systems [1][2][3][4]. Systems that gather data in separate IR spectral bands can discriminate both absolute temperature and unique signatures of objects in the scene.…”
Section: Introductionmentioning
confidence: 99%